NEUROTIC TRENDS OF TONYA HARDING IN I, TONYA MOVIE - Olivia Olivia; Putri Rindu Kinasih (PARADIGM: Journal of Language and Literary Studies, 2023)
Psychological issue namely neurotics has always been an important matter in human life since long ago. There have been several literary works that represent this psychological issue. From many of those works which portray psychological problems, I, Tonya is one of the representative works. In this research, the writer did a film study by using the psychoanalysis approach. The source of the data is the script and scenes of the I, Tonya movie. From the research, it can be concluded that a neurotic personality is shaped due to several aspects. Tonya Harding's childhood and culture had an impact on how she behaved as an adult. Because of her experiences as a child and the competitive culture of American citizens, she develops an aggressive personality. We can infer that Tonya's neurotic trend is gravitating away from people who behave aggressively. Instead of being a survivor, Tonya ended up as an aggressive and hostile person. In conclusion, Tonya was only able to use one neurotic trend, acting violently and manipulatively, as a coping method because of her childhood and culture.